Hollow resin particle and method for producing the same
Patent Information
- Application Number
- JP2024195225
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-29
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-10-16
AI Technical Summary
【0017】 本発明の実施形態によれば、樹脂層に空域を導入して、低誘電化、低誘電正接化を可能とする中空樹脂粒子であって、中空部分を簡易に形成させて得ることができる、中空樹脂粒子を提供することができる。また、そのような中空樹脂粒子を簡易に製造する方法を提供することができる。
Smart Images

Figure 2025016758000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to hollow resin particles and a method for producing the same. [Background technology]
[0002] In order to increase the speed of information processing using electronic devices, attempts have been made to reduce the dielectric constant and dielectric loss tangent of the insulating layer of a multilayer printed circuit board. As part of these attempts, studies have been made to introduce air space into the resin layer by mixing hollow particles, each of which has a shell portion and a hollow portion surrounded by the shell portion, into a thermosetting resin, thereby reducing the dielectric constant and dielectric loss tangent.
[0003] It has been reported that hollow particles can be obtained by suspension polymerization of a monomer mainly composed of an acrylic polyfunctional monomer such as trimethylolpropane tri(meth)acrylate or dipentaerythritol hexaacrylate together with a hydrophobic solvent (Patent Document 1).
[0004] In general, acrylic resins are known to have high relative dielectric constants and dielectric loss tangents, and for this reason, the acrylic hollow resin particles described in Patent Document 1 are not suitable for the purpose of reducing the dielectric constant and dielectric loss tangent of a resin layer.
[0005] It has also been reported that hollow particles, for example, can be obtained by suspension polymerization of divinylbenzene together with saturated hydrocarbons having 8 to 18 carbon atoms (specifically, hexadecane) to produce styrene-based hollow resin particles (Patent Document 2).
[0006] The styrene-based hollow resin particles described in Patent Document 2 are made of a material (crosslinked polystyrene) that has a lower relative dielectric constant and dielectric loss tangent than acrylic hollow resin particles. Therefore, they are effective particles for the purpose of reducing the dielectric constant and dielectric loss tangent of the resin layer. However, since saturated hydrocarbons having 8 to 18 carbon atoms (specifically, hexadecane) are used in the production thereof, it is difficult to remove the solvent from the hollow portion by distillation or the like, and saturated hydrocarbons having 8 to 18 carbon atoms remain in the obtained styrene-based hollow resin particles, making it difficult to obtain styrene-based hollow resin particles in which the hollow portion is completely replaced with air. In addition, in order to obtain styrene-based hollow resin particles in which the hollow portion is completely replaced with air, production costs are required for the above-mentioned solvent removal. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6513273 [Patent Document 2] JP 2002-080503 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above-mentioned problems of the prior art, and its main object is to provide hollow resin particles that can be obtained by simply forming a hollow portion, and that can have a low dielectric constant and a low dielectric loss tangent by introducing an air space into a resin layer. It is also an object of the present invention to provide a method for easily producing such hollow resin particles. [Means for solving the problem]
[0009] The hollow resin particles according to an embodiment of the present invention are A hollow resin particle having a shell portion and a hollow portion surrounded by the shell portion, The shell portion contains an aromatic polymer (P1) obtained by polymerizing a monomer composition containing an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1). [ka] (R 1 represents H or CH3, R 2 represents H, an alkyl group, or a phenyl group, and R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms, and m represents the average number of moles of the oxyalkylene group added, which is a number from 1 to 100.
[0010] In one embodiment, the oxyalkylene group is at least one selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group.
[0011] In one embodiment, the monomer composition contains 10% by weight to 70% by weight of an aromatic crosslinkable monomer (a), 10% by weight to 70% by weight of an aromatic monofunctional monomer (b), and 0.5% by weight to 30% by weight of a (meth)acrylic acid ester monomer (c) represented by general formula (1).
[0012] In one embodiment, the shell portion contains the aromatic polymer (P1) and further contains a non-crosslinkable polymer (P2) which is at least one selected from the group consisting of polyolefins, styrene-based polymers, (meth)acrylic acid-based polymers, and styrene-(meth)acrylic acid-based polymers.
[0013] In one embodiment, the aromatic crosslinking monomer (a) is divinylbenzene.
[0014] In one embodiment, the aromatic monofunctional monomer (b) is at least one selected from the group consisting of styrene and ethylvinylbenzene.
[0015] A method for producing hollow resin particles according to an embodiment of the present invention includes the steps of: A method for producing hollow resin particles according to an embodiment of the present invention, comprising the steps of: A monomer composition containing an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1), a polymerization initiator, and an organic mixed solution containing an organic solvent having a boiling point of less than 100°C are dispersed in an aqueous solution containing at least one selected from the group consisting of a dispersion stabilizer and a surfactant, and suspension polymerization is performed. [ka] (R 1 represents H or CH3, R 2 represents H, an alkyl group, or a phenyl group, and R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms, and m represents the average number of moles of the oxyalkylene group added, which is a number from 1 to 100.
[0016] Semiconductor materials according to embodiments of the present invention include hollow resin particles according to embodiments of the present invention. Effect of the Invention
[0017] According to an embodiment of the present invention, it is possible to provide hollow resin particles that can be obtained by simply forming a hollow portion by introducing an air space into a resin layer, thereby enabling a reduction in dielectric constant and a reduction in dielectric loss tangent, and it is also possible to provide a method for easily producing such hollow resin particles. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a TEM photograph of the hollow resin particles (1) obtained in Example 1. [Diagram 2] FIG. 2 is a TEM photograph of the hollow resin particles (2) obtained in Example 2. [Diagram 3] FIG. 2 is a TEM photograph of the hollow resin particles (3) obtained in Example 3. [Figure 4]FIG. 2 is a TEM photograph of the hollow resin particles (4) obtained in Example 4. [Diagram 5] FIG. 1 is a TEM photograph of hollow resin particles (5) obtained in Example 5. [Figure 6] FIG. 2 is a TEM photograph of the hollow resin particles (6) obtained in Example 6. [Figure 7] FIG. 1 is a TEM photograph of hollow resin particles (7) obtained in Example 7. [Figure 8] FIG. 1 is a TEM photograph of hollow resin particles (8) obtained in Example 8. [Figure 9] FIG. 1 is a TEM photograph of hollow resin particles (9) obtained in Example 9. [Figure 10] FIG. 2 is a TEM photograph of the hollow resin particles (10) obtained in Example 10. [Figure 11] FIG. 1 is a TEM photograph of hollow resin particles (11) obtained in Example 11. [Figure 12] FIG. 1 is a TEM photograph of hollow resin particles (12) obtained in Example 12. [Figure 13] FIG. 2 is a TEM photograph of particles (C1) obtained in Comparative Example 1. [Figure 14] FIG. 2 is a TEM photograph of particles (C2) obtained in Comparative Example 2. [Figure 15] FIG. 2 is a TEM photograph of particles (C3) obtained in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0020] ≪≪1. Hollow resin particles≫≫ ≪1-1. Structure of hollow resin particles≫ The hollow resin particles according to the embodiment of the present invention are hollow resin particles having a shell portion and a hollow portion surrounded by the shell portion. Here, "hollow" means that the inside is filled with a substance other than resin, such as a gas or liquid, and preferably means that the inside is filled with a gas in order to more effectively exhibit the effects of the present invention.
[0021] The hollow portion may be composed of one hollow region or multiple hollow regions, but it is preferable that the hollow portion be composed of one hollow region, from the viewpoint of preventing the resin component constituting the shell from entering the hollow portion of the substrate or the like due to the relatively large amount of the resin component constituting the shell.
[0022] The average particle diameter of the hollow resin particles is preferably 0.1 μm to 5.0 μm, more preferably 0.15 μm to 1.0 μm, even more preferably 0.2 μm to 0.8 μm, and particularly preferably 0.3 μm to 0.6 μm. When the average particle diameter of the hollow resin particles is within the above range, the effect of the present invention can be more effectively exhibited. When the average particle diameter of the hollow resin particles is less than 0.1 μm, the thickness of the shell portion becomes relatively thin, and the hollow resin particles may not have sufficient strength. When the average particle diameter of the hollow resin particles is more than 5.0 μm, phase separation between the polymer and the solvent produced by polymerization of the monomer component during suspension polymerization may be difficult to occur, which may make it difficult to form the shell portion.
[0023] ≪1-2.Shell part≫ The shell portion includes an aromatic polymer (P1) obtained by polymerizing a monomer composition including an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c). The effect of the present invention can be realized by the shell portion including an aromatic polymer (P1) obtained by polymerizing a monomer composition including an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c). In particular, the effect of the present invention can be realized by adopting a (meth)acrylic acid ester monomer (c) having a specific structure as a monomer constituting the aromatic polymer (P1).
[0024] The content of the aromatic polymer (P1) in the shell portion is preferably 60% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 80% by weight to 100% by weight, and particularly preferably 90% by weight to 100% by weight, in order to further exert the effects of the present invention.
[0025] <Aromatic polymer (P1)> The aromatic polymer (P1) is obtained by polymerizing a monomer composition containing an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c). That is, the aromatic polymer (P1) has a structural unit derived from the aromatic crosslinkable monomer (a), a structural unit derived from the aromatic monofunctional monomer (b), and a structural unit derived from the (meth)acrylic acid ester monomer (c).
[0026] In terms of being able to more effectively exhibit the effects of the present invention, the monomer composition preferably contains 10% by weight to 70% by weight of the aromatic crosslinkable monomer (a), 10% by weight to 70% by weight of the aromatic monofunctional monomer (b), and 0.5% by weight to 30% by weight of the (meth)acrylic acid ester monomer (c), and more preferably contains 20% by weight to 65% by weight of the aromatic crosslinkable monomer (a), 20% by weight to 65% by weight of the aromatic monofunctional monomer (b), and 10% by weight of the (meth)acrylic acid ester monomer (c). % by weight to 25% by weight, more preferably 30% by weight to 60% by weight of aromatic crosslinkable monomer (a), 30% by weight to 60% by weight of aromatic monofunctional monomer (b), and 1.5% by weight to 20% by weight of (meth)acrylic acid ester monomer (c), and particularly preferably 40% by weight to 50% by weight of aromatic crosslinkable monomer (a), 40% by weight to 50% by weight of aromatic monofunctional monomer (b), and 2% by weight to 15% by weight of (meth)acrylic acid ester monomer (c).
[0027] The monomer composition contains an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c). The total content of the aromatic crosslinkable monomer (a), the aromatic monofunctional monomer (b), and the (meth)acrylic acid ester monomer (c) in the monomer composition is preferably 80% by weight to 100% by weight, more preferably 85% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, and particularly preferably 95% by weight to 100% by weight, in order to further exhibit the effects of the present invention.
[0028] The monomer composition may contain any appropriate other monomer other than the aromatic crosslinkable monomer (a), the aromatic monofunctional monomer (b), and the (meth)acrylic acid ester monomer (c) within a range that does not impair the effects of the present invention. The other monomer may be one type only or two or more types.
[0029] (Aromatic Crosslinking Monomer (a)) As long as the aromatic crosslinkable monomer (a) is an aromatic monomer having crosslinkability, any suitable aromatic crosslinkable monomer can be adopted within the scope of not impairing the effects of the present invention. As such aromatic crosslinkable monomer (a), in terms of being able to further express the effects of the present invention, for example, divinylbenzene, divinylnaphthalene, diallyl phthalate, etc. can be mentioned. In terms of being able to further express the effects of the present invention and in terms of reactivity, divinylbenzene is preferred as the aromatic crosslinkable monomer (a).
[0030] The aromatic crosslinkable monomer (a) may be of only one type, or of two or more types.
[0031] (Aromatic Monofunctional Monomer (b)) As long as the aromatic monofunctional monomer (b) is a monofunctional aromatic monomer, any appropriate aromatic monofunctional monomer can be adopted within a range that does not impair the effects of the present invention. Examples of such aromatic monofunctional monomers (b) include styrene, ethylvinylbenzene, α-methylstyrene, vinyltoluene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, vinylbiphenyl, and vinylnaphthalene, which can further exhibit the effects of the present invention. From the viewpoint of further exhibiting the effects of the present invention and from the viewpoint of reactivity, the aromatic monofunctional monomer (b) is preferably at least one selected from the group consisting of styrene and ethylvinylbenzene.
[0032] The aromatic monofunctional monomer (b) may be of one type only, or of two or more types.
[0033] ((Meth)acrylic acid ester monomer (c)) The (meth)acrylic acid ester monomer (c) is represented by the formula (1). [ka]
[0034] In formula (1), R 1 represents H or CH3.
[0035] In formula (1), R 2 represents H, an alkyl group, or a phenyl group.
[0036] In formula (1), R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms. 3 represents an alkylene group having 2 to 18 carbon atoms.
[0037] In formula (1), R 3 -O is an oxyalkylene group having 2 to 18 carbon atoms, preferably an oxyalkylene group having 2 to 8 carbon atoms, and more preferably an oxyalkylene group having 2 to 4 carbon atoms. 3When -O is any two or more selected from an oxyethylene group, an oxypropylene group, an oxybutylene group, etc., R 3 The addition form of -O may be any of random addition, block addition, alternating addition, etc. The addition form referred to here means the form itself, and does not mean that it must be obtained by an addition reaction.
[0038] In formula (1), R 3 -O is at least one selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group (typically, an oxytetramethylene group), in that the effects of the present invention can be more effectively exhibited.
[0039] In formula (1), m represents the average number of moles of oxyalkylene groups added (sometimes referred to as "chain length"). m is a number from 1 to 100, preferably a number from 1 to 40, more preferably a number from 2 to 30, even more preferably a number from 3 to 20, particularly preferably a number from 4 to 18, and most preferably a number from 5 to 15. When m is within the above range, the effects of the present invention can be more effectively exhibited.
[0040] In formula (1), R 3 When -O is two or more types, for example, when it is composed of an oxyethylene group (C2H4O) and an oxypropylene group (C3H6O), m is the sum of the average number of moles of each oxyalkylene group added. 3 -O) m - is -[(C2H4O) p (C3H6O) q ]- (as described above, the addition may be in any form such as random addition, block addition, or alternating addition), then m=p+q.
[0041] Examples of the (meth)acrylic acid ester monomer (c), from the viewpoint of further exhibiting the effects of the present invention, include methoxypolyethylene glycol methacrylate, ethoxypolyethylene glycol methacrylate, propoxypolyethylene glycol methacrylate, butoxypolyethylene glycol methacrylate, hexaoxypolyethylene glycol methacrylate, octoxypolyethylene glycol polypropylene glycol methacrylate, lauroxypolyethylene glycol methacrylate, stearoxypolyethylene glycol methacrylate, phenoxypolyethylene glycol polypropylene glycol methacrylate, methoxypolyethylene glycol acrylate, polyethylene glycol monomethacrylate, polypropylene glycol monomethacrylate, polyethylene glycol propylene glycol monomethacrylate, polyethylene glycol tetramethylene glycol monomethacrylate, propylene glycol polybutylene glycol monomethacrylate, monoethylene glycol monoacrylate, and polypropylene glycol monoacrylate.
[0042] As the (meth)acrylic acid ester monomer (c), commercially available products can be used, for example, the "Blenmer" series manufactured by NOF Corporation.
[0043] The (meth)acrylic acid ester monomer (c) may be of one type alone or of two or more types.
[0044] <Non-crosslinkable polymer (P2)> The shell portion may contain an aromatic polymer (P1) and further contain a non-crosslinkable polymer (P2) which is at least one selected from the group consisting of polyolefins, styrene-based polymers, (meth)acrylic acid-based polymers, and styrene-(meth)acrylic acid-based polymers.
[0045] The content of the non-crosslinkable polymer (P2) in the shell portion is preferably 0 to 40% by weight, more preferably 0 to 30% by weight, even more preferably 0 to 20% by weight, and particularly preferably 0 to 10% by weight, in order to further exert the effects of the present invention.
[0046] Examples of polyolefins include polyethylene, polypropylene, polyα-olefins, etc. From the viewpoint of solubility in the monomer composition, it is preferable to use a side-chain crystalline polyolefin using a long-chain α-olefin as a raw material, a low-molecular-weight polyolefin produced with a metallocene catalyst, or an olefin oligomer.
[0047] Examples of styrene-based polymers include polystyrene, styrene-acrylonitrile copolymers, and acrylonitrile-butadiene-styrene copolymers.
[0048] Examples of the (meth)acrylic acid-based polymer include polymethyl(meth)acrylate, polyethyl(meth)acrylate, polybutyl(meth)acrylate, and polypropyl(meth)acrylate.
[0049] Examples of styrene-(meth)acrylic acid polymers include styrene-methyl (meth)acrylate copolymers, styrene-ethyl (meth)acrylate copolymers, styrene-butyl (meth)acrylate copolymers, and styrene-propyl (meth)acrylate copolymers.
[0050] ≪1-3. Dielectric constant of hollow resin particles≫ The dielectric constant of the hollow resin particles according to the embodiment of the present invention is preferably 1.0 to 2.5, more preferably 1.0 to 2.4, and even more preferably 1.0 to 2.3. When the dielectric constant of the hollow resin particles according to the embodiment of the present invention is within the above range, the effects of the present invention can be more effectively exhibited. When the dielectric constant of the hollow resin particles according to the embodiment of the present invention exceeds 2.5, even if the hollow resin particles are mixed with, for example, a thermosetting resin, a sufficient dielectric reduction effect cannot be obtained.
[0051] The dielectric constant of the hollow resin particles according to the embodiment of the present invention can be calculated, for example, by referring to "Dielectric Constant of a Mixture" (Applied Physics, Vol. 27, No. 8 (1958)). If the dielectric constant of the mixture of the dispersion medium and hollow resin particles is ε, the dielectric constant of the base material (e.g., a resin composition such as polyimide or epoxy) serving as the dispersion medium is ε1, the dielectric constant of the hollow resin particles is ε2, and the volume fraction of the hollow resin particles in the mixture is φ, the following formula is established. In other words, if ε, ε1, and φ are experimentally determined, the dielectric constant ε2 of the hollow resin particles can be calculated.
number
[0052] The volume fraction φ of the hollow resin particles in the mixture of the dispersion medium and the hollow resin particles can be determined as follows.
number
[0053] The density of the hollow resin particles was measured using a pycnometer (Cotec Co., Ltd., TQC 50 mL specific gravity bottle) and a liquid polymer, ARUFON UP-1080 (Toa Gosei Co., Ltd., density 1.05 g / cm 3 ) can be experimentally determined. Specifically, hollow resin particles and ARUFON UP-1080 are defoamed and mixed using a planetary mixer defoamer (KURABO Corp., Mazerustar KK-250) so that the ratio of hollow resin particles is 10% by weight, to prepare a mixture for evaluation. The mixture for evaluation is filled into a 50 mL pycnometer, and the weight of the filled mixture for evaluation is calculated by subtracting the weight of the empty pycnometer from the weight of the pycnometer filled with the mixture. The density of the hollow resin particles can be calculated from this value using the following formula.
number
[0054] <1-4. Uses of hollow resin particles> The hollow resin particles according to the embodiment of the present invention can be used in various applications. In terms of being able to utilize the effects of the present invention more effectively, the hollow resin particles according to the embodiment of the present invention are suitable for semiconductor materials such as interlayer insulating films, dry film resists, solder resists, bonding wires, magnet wires, semiconductor encapsulants, epoxy encapsulants, mold underfills, underfills, die bond pastes, buffer coating materials, copper-clad laminates, and flexible substrates. Among these, the hollow resin particles according to the embodiment of the present invention are particularly suitable for semiconductor materials such as interlayer insulating films, solder resists, magnet wires, epoxy encapsulants, underfills, buffer coating materials, copper-clad laminates, and flexible substrates. By adding the hollow resin particles according to the embodiment of the present invention to, for example, polyphenylene ether, polyimide, polybismaleimide, and epoxy resins that are generally used in such semiconductor materials, it is possible to achieve low dielectric constant and low dielectric loss tangent. That is, the semiconductor material according to the embodiment of the present invention includes the hollow resin particles according to the embodiment of the present invention. The hollow resin particles according to the embodiment of the present invention can also be used in applications such as paint compositions, cosmetics, paper coating compositions, heat insulating compositions, light diffusing compositions, and light diffusing films.
[0055] 2. Method for producing hollow resin particles A method for producing hollow resin particles according to an embodiment of the present invention comprises dispersing a monomer composition containing an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1), a polymerization initiator, and an organic mixed solution containing an organic solvent having a boiling point of less than 100°C, in an aqueous solution containing at least one selected from the group consisting of a dispersion stabilizer and a surfactant, and carrying out suspension polymerization. [ka] (R 1 represents H or CH3, R 2 represents H, an alkyl group, or a phenyl group, and R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms, and m represents the average number of moles of the oxyalkylene group added, which is a number from 1 to 100.
[0056] Dispersion of the organic mixed solution in the aqueous solution is not particularly limited, and can be carried out by any known method, so long as the organic mixed solution can be present in the aqueous solution in the form of droplets.
[0057] In the method for producing hollow resin particles according to an embodiment of the present invention, the monomer composition contained in the organic mixed solution contains the aromatic crosslinkable monomer (a), the aromatic monofunctional monomer (b), and the (meth)acrylic acid ester monomer (c). This allows the use of an organic solvent having a boiling point of less than 100°C as the organic solvent used in the suspension polymerization, making it easier to remove the solvent from the hollow portions of the obtained hollow resin particles, and enabling production costs to be reduced.
[0058] ≪2-1. Aqueous solution (aqueous phase)≫ The aqueous solution contains an aqueous medium and at least one selected from the group consisting of a dispersion stabilizer and a surfactant.
[0059] Examples of the aqueous medium include water and a mixed medium of water and a lower alcohol (methanol, ethanol, etc.).
[0060] Examples of the dispersion stabilizer include polyvinyl alcohol, polycarboxylic acid, celluloses (hydroxyethyl cellulose, carboxymethyl cellulose, etc.), polyvinylpyrrolidone, etc. In addition, inorganic water-soluble polymer compounds such as sodium tripolyphosphate can also be used in combination. In addition, phosphates such as calcium phosphate, magnesium phosphate, aluminum phosphate, and zinc phosphate; pyrophosphates such as calcium pyrophosphate, magnesium pyrophosphate, aluminum pyrophosphate, and zinc pyrophosphate; poorly water-soluble inorganic compounds such as calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, and colloidal silica; and the like can also be used.
[0061] The amount of the dispersion stabilizer added is preferably 0.5 parts by weight to 10 parts by weight with respect to 100 parts by weight of the organic mixed solution. The dispersion stabilizer may be of only one kind, or of two or more kinds.
[0062] Examples of the surfactant include anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.
[0063] Examples of the anionic surfactant include non-reactive anionic surfactants such as alkyl sulfate fatty acid salts, alkylbenzenesulfonates, alkylnaphthalenesulfonates, alkanesulfonates, alkyldiphenylethersulfonates, dialkylsulfosuccinates, monoalkylsulfosuccinates, and polyoxyethylene alkylphenylether phosphates; and reactive anionic surfactants such as polyoxyethylene-1-(allyloxymethyl)alkylether sulfate ammonium salts, polyoxyethylene alkylpropenylphenylether sulfate ammonium salts, and polyoxyalkylene alkenyl ether ammonium sulfate.
[0064] Examples of the cationic surfactant include alkyltrimethylammonium salts, alkyltriethylammonium salts, dialkyldimethylammonium salts, dialkyldiethylammonium salts, and N-polyoxyalkylene-N,N,N-trialkylammonium salts.
[0065] Examples of the zwitterionic surfactant include lauryl dimethylamine oxide, phosphate salts, and phosphite surfactants.
[0066] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polysorbitan fatty acid esters, polyoxyethylene alkylamines, glycerin fatty acid esters, and oxyethylene-oxypropylene block polymers.
[0067] The amount of the surfactant added is preferably 0.01 part by weight to 1 part by weight with respect to 100 parts by weight of the organic mixed solution. The surfactant may be one type only, or two or more types may be used.
[0068] The aqueous solution may contain any appropriate other components as long as the effects of the present invention are not impaired.
[0069] ≪2-2. Organic mixed solution (oil phase)≫ The organic mixed solution contains a monomer composition including an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c), a polymerization initiator, and an organic solvent having a boiling point of less than 100°C.
[0070] As for the monomer composition contained in the organic mixed solution, the explanation in the section <Aromatic polymer (P1)> in <<1-2. Shell portion>> of <<1. Hollow resin particles>> can be directly applied.
[0071] As the polymerization initiator, any suitable polymerization initiator can be adopted within the scope that does not impair the effect of the present invention. Examples of such polymerization initiators include organic peroxides such as lauroyl peroxide, benzoyl peroxide, orthochlorobenzoyl peroxide, orthomethoxybenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and di-t-butyl peroxide; azo compounds such as 2,2'-azobisisobutyronitrile, 1,1'-azobiscyclohexanecarbonitrile, and 2,2'-azobis(2,4-dimethylvaleronitrile); and the like.
[0072] The amount of the polymerization initiator added is preferably within a range of 0.1 to 5 parts by weight based on 100 parts by weight of the monomer composition. The polymerization initiator may be of only one kind, or of two or more kinds.
[0073] Examples of organic solvents having a boiling point of less than 100° C. that are suitable for use in the method for producing hollow resin particles according to an embodiment of the present invention include heptane, hexane, cyclohexane, methyl acetate, ethyl acetate, methyl ethyl ketone, chloroform, and carbon tetrachloride.
[0074] The organic solvent having a boiling point of less than 100° C. may be a mixed solvent.
[0075] The amount of the organic solvent having a boiling point of less than 100° C. added is preferably 20 parts by weight to 250 parts by weight based on 100 parts by weight of the monomer composition.
[0076] The organic mixed solution may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of such other components include the non-crosslinkable polymer (P2) in 1-2. Shell part of 1. Hollow resin particles.
[0077] The amount of the non-crosslinkable polymer (P2) added is preferably 0 to 67 parts by weight based on 100 parts by weight of the monomer composition. The non-crosslinkable polymer (P2) may be one kind or two or more kinds.
[0078] <2-3. Suspension polymerization> Hollow resin particles are obtained by dispersing the organic mixture in an aqueous solution and polymerizing the resulting suspension, preferably with post-heating.
[0079] As long as the organic mixed solution can be present in the form of droplets in the aqueous solution, any suitable dispersion method can be adopted within the scope of the invention, which does not impair the effects of the present invention. A representative dispersion method is a dispersion method using a homogenizer, such as an ultrasonic homogenizer or a high-pressure homogenizer.
[0080] The polymerization temperature may be any suitable temperature suitable for suspension polymerization within a range that does not impair the effects of the present invention. Such a polymerization temperature is preferably 30°C to 80°C.
[0081] The polymerization time may be any appropriate time suitable for suspension polymerization, as long as it does not impair the effects of the present invention. Such a polymerization time is preferably 1 hour to 20 hours.
[0082] Post-heating, which is preferably carried out after polymerization, is a treatment suitable for obtaining hollow resin particles with a high degree of perfection.
[0083] The temperature of post-heating preferably carried out after polymerization may be any appropriate temperature within a range that does not impair the effects of the present invention. The temperature of such post-heating is preferably 70°C to 120°C.
[0084] The time for post-heating preferably carried out after polymerization can be any appropriate time within the range not impairing the effects of the present invention, and the time for such post-heating is preferably 1 hour to 10 hours. EXAMPLES
[0085] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".
[0086] (Average particle size) The Z-average particle diameter of the hollow resin particles or particles was measured using a dynamic light scattering method, and the measured Z-average particle diameter was taken as the average particle diameter of the obtained hollow resin particles or particles. That is, the obtained hollow resin particles or particles in a slurry state were first diluted with ion-exchanged water, and the aqueous dispersion adjusted to 0.1% by weight was irradiated with laser light, and the intensity of the scattered light from the hollow resin particles or particles was measured in microseconds. The scattering intensity distribution caused by the detected hollow resin particles or particles was then fitted to a normal distribution, and the Z-average particle size of the hollow resin particles or particles was obtained by cumulant analysis to calculate the average particle size. This Z-average particle size can be easily measured using a commercially available particle size measuring device. In the following examples and comparative examples, the Z-average particle size was measured using a particle size measuring device (Zetasizer Nano ZS manufactured by Malvern Instruments). Usually, commercially available particle size measuring devices are equipped with data analysis software, and the data analysis software can automatically analyze the measurement data to calculate the Z-average particle size.
[0087] (TEM measurement: Observation of the presence or absence of hollow resin particles or particles and their shape) The hollow resin particles or particles as dry powder were surface treated (10 Pa, 5 mA, 10 seconds) using a coating device "Osmium Coater Neoc-Pro" manufactured by Meiwa Force Systems. The hollow resin particles or particles were then observed with a TEM (transmission electron microscope, Hitachi High-Technologies Corporation H-7600) to confirm the presence or absence of hollowness and the shape of the hollow resin particles or particles. At this time, the accelerating voltage was set to 80 kV, and the magnification was set to 5,000 times or 10,000 times.
[0088] Example 1 Styrene (St) 1.15 g, divinylbenzene (DVB) 810 (Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) 1.85 g, heptane 2.4 g, HS Crystal 4100 (side chain crystalline polyolefin, Toyokuni Oil Co., Ltd.) 0.3 g, Blenmar 50PEP-300 (polyethylene glycol propylene glycol monomethacrylate (in formula (1), R 1 =CH3, R 2 =H, (R 3 -O) m =[(C2H4O) 3.5 (C3H6O) 2.5 ], random addition form, NOF Corporation) 0.3 g, and Perloyl L (polymerization initiator, NOF Corporation) 0.099 g were mixed to prepare an oil phase. Next, 34 g of ion-exchanged water and 0.017 g of Rapisol A-80 (surfactant, NOF Corporation) were mixed to prepare an aqueous phase. The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer (SONIFIER450, manufactured by BRANSON, conditions: Duty Cycle=50%, Output Control=5, processing time 3 minutes). The suspension was polymerized by heating at 70°C for 4 hours to obtain a slurry. The slurry was heated at 100°C for 24 hours to obtain hollow resin particles (1) as a dry powder. The average particle diameter of the obtained hollow resin particles (1) was 356 nm, and the particle density was 0.65 g / cm. 3 The results of TEM observation of the obtained hollow resin particles (1) are shown in FIG. 1. It was confirmed that the hollow resin particles (1) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0089] Example 2 Hollow resin particles (2) were obtained by carrying out the same operation as in Example 1, except that styrene was 0.92 g, divinylbenzene 810 was 1.48 g, heptane was 3.0 g, and Peroyl L was 0.10 g. The average particle diameter of the obtained hollow resin particles (2) was 382 nm, and the particle density was 0.64 g / cm. 3 The results of TEM observation of the obtained hollow resin particles (2) are shown in FIG. 2. It was confirmed that the hollow resin particles (2) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0090] Example 3 Hollow resin particles (3) were obtained by carrying out the same operation as in Example 1, except that styrene was 1.49 g, divinylbenzene 810 was 2.41 g, heptane was 1.5 g, and Peroyl L was 0.126 g. The average particle diameter of the obtained hollow resin particles (3) was 329 nm, and the particle density was 0.69 g / cm. 3 The results of TEM observation of the obtained hollow resin particles (3) are shown in FIG. 3. It was confirmed that the hollow resin particles (3) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0091] Example 4 Hollow resin particles (4) were obtained by carrying out the same operations as in Example 1, except that 1.19 g of styrene, 1.93 g of divinylbenzene 810, 0.10 g of Peroyl L, and 0.18 g of polystyrene (PS) (non-crosslinked, weight average molecular weight 300,000) were used instead of 0.3 g of HS Crysta 4100 (side chain crystalline polyolefin, Toyokuni Oil Mills). The average particle diameter of the obtained hollow resin particles (4) was 390 nm, and the particle density was 0.67 g / cm. 3 The results of TEM observation of the obtained hollow resin particles (4) are shown in FIG. 4. It was confirmed that the hollow resin particles (4) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0092] Example 5 Hollow resin particles (5) were obtained by the same operation as in Example 1, except that the amount of Blenmar 50PEP-300 was 0.6 g and HS Crysta 4100 was not used. The average particle diameter of the obtained hollow resin particles (5) was 310 nm. The TEM observation result of the obtained hollow resin particles (5) is shown in FIG. 5. It was confirmed that the hollow resin particles (5) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0093] Example 6 Blenmer 50PEP-300 (polyethylene glycol propylene glycol monomethacrylate (in formula (1), R 1 =CH3, R 2 =H, (R 3 -O) m =[(C2H4O) 3.5 (C3H6O) 2.5 ], random addition form), NOF Corporation) 0.3 g, instead of Blenmar PME-100 (polyethylene glycol methacrylate (in formula (1), R 1 =CH3, R 2 =CH3, (R 3 -O) mHollow resin particles (6) were obtained by carrying out the same operation as in Example 1, except that 0.3 g of dimethylformamide (C2H4O) (NOF Corporation) was used. The average particle diameter of the obtained hollow resin particles (6) was 520 nm. The TEM observation result of the obtained hollow resin particles (6) is shown in FIG. 6. It was confirmed that the hollow resin particles (6) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0094] Example 7 Hollow resin particles (7) were obtained by carrying out the same operation as in Example 3, except that 0.3 g of Blenmer PME-100 was used instead of 0.3 g of Blenmer 50PEP-300. The average particle diameter of the obtained hollow resin particles (7) was 501 nm and the particle density was 0.63 g / cm. 3 The results of TEM observation of the obtained hollow resin particles (7) are shown in FIG. 7. It was confirmed that the hollow resin particles (7) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0095] Example 8 Instead of using 0.3 g of Blenmer 50 PEP-300, Blenmer 55 PET-800 (polyethylene glycol tetramethylene glycol monomethacrylate (R 1 =CH3, R 2 =H, (R 3 -O) m =[(C2H4O) 10 Hollow resin particles (8) were obtained by the same procedure as in Example 3, except that 0.3 g of dimethylformamide (C4H8O)5], random addition form) was used. The average particle diameter of the obtained hollow resin particles (8) was 325 nm. The TEM observation result of the obtained hollow resin particles (8) is shown in FIG. 8. It was confirmed that the hollow resin particles (8) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0096] Example 9 Hollow resin particles (9) were obtained by carrying out the same operation as in Example 3, except that 0.0081 g of Cortamine 86W (surfactant, Kao Corporation) was used instead of 0.017 g of Lapisol A-80. The average particle diameter of the obtained hollow resin particles (9) was 539 nm. The TEM observation result of the obtained hollow resin particles (9) is shown in FIG. 9. It was confirmed that the hollow resin particles (9) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0097] Example 10 Hollow resin particles (10) were obtained by carrying out the same operation as in Example 3, except that 0.034 g of Adekamin 4MAC-30 (surfactant, ADEKA Corporation) was used instead of 0.017 g of Lapisol A-80. The average particle diameter of the obtained hollow resin particles (10) was 430 nm. The TEM observation result of the obtained hollow resin particles (10) is shown in FIG. 10. It was confirmed that the hollow resin particles (10) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0098] Example 11 Hollow resin particles (11) were obtained by carrying out the same operation as in Example 3, except that 0.0076 g of Adekamin 4MAC-30 was used instead of 0.017 g of Lapisol A-80. The average particle diameter of the obtained hollow resin particles (11) was 1270 nm. The TEM observation result of the obtained hollow resin particles (11) is shown in FIG. 11. It was confirmed that the hollow resin particles (11) were hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0099] Example 12 Hollow resin particles (12) were obtained by the same operation as in Example 3, except that 1.38 g of styrene, 2.22 g of divinylbenzene 810, 1.5 g of cyclohexane instead of heptane, 0.6 g of HS Crysta 4100, 0.054 g of Peroyl L, and 0.0085 g of Lapisol A-80 were used. The average particle diameter of the obtained hollow resin particles (12) was 416 nm. The TEM observation result of the obtained hollow resin particles (12) is shown in FIG. 12. It was confirmed that the hollow resin particles (12) were hollow resin particles having a hollow surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0100] Comparative Example 1 An oil phase was prepared by mixing 1.74 g of methyl methacrylate (MMA), 1.74 g of dipentaerythritol hexaacrylate (ADPH) (Shin-Nakamura Chemical Co., Ltd.), 2.4 g of toluene, 0.126 g of polystyrene (non-crosslinked, weight average molecular weight 300,000), and 0.104 g of Perloyl L (polymerization initiator, NOF Corporation). Next, 34 g of ion-exchanged water and 0.034 g of Rapisol A-80 (surfactant, NOF Corporation) were mixed to prepare an aqueous phase. The oil phase was added to the aqueous phase, and a suspension was prepared using an ultrasonic homogenizer (SONIFIER450, manufactured by BRANSON, conditions: Duty Cycle = 50%, Output Control = 5, processing time 3 minutes). The suspension was polymerized by heating at 70 °C for 4 hours to obtain a slurry. The slurry was heated at 100 °C for 24 hours to obtain particles (C1) as a dry powder. The average particle size of the obtained particles (C1) was 478 nm, and the particle density was 0.614 g / cm 3 The results of TEM observation of the obtained particles (C1) are shown in FIG. 13. It was confirmed that the particles (C1) were hollow resin particles having a cavity surrounded by a shell. The blending amounts and other information are shown in Table 1.
[0101] Comparative Example 2 Particles (C2) were obtained by carrying out the same operations as in Example 1, except that 1.31 g of styrene, 2.11 g of divinylbenzene 810, 0.10 g of Peroyl L, and 0.18 g of polystyrene (non-crosslinked, weight average molecular weight 300,000) were used instead of 0.3 g of HS Crysta 4100 (side chain crystalline polyolefin, Toyokuni Oil Co., Ltd.), and 0.36 g of reactive surfactant RN2025 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were added to the aqueous phase without using Blenmar 50PEP-300. The average particle diameter of the obtained particles (C2) was 350 nm. The TEM observation results of the obtained particles (C2) are shown in FIG. 14. It was confirmed that the particles (C2) were not hollow resin particles having a hollow space surrounded by a shell. The blending amounts and the like are shown in Table 1.
[0102] Comparative Example 3 Particles (C3) were obtained by carrying out the same operations as in Example 1, except that 1.38 g of styrene, 2.22 g of divinylbenzene 810, 0.10 g of Peroyl L, 0.18 g of polystyrene (non-crosslinked, weight average molecular weight 300,000) were used, and HS Crysta 4100 and Blenmar 50 PEP-300 were not used. The average particle diameter of the obtained particles (C3) was 430 nm. The TEM observation results of the obtained particles (C3) are shown in FIG. 15. It was confirmed that the particles (C3) were not hollow resin particles having a hollow space surrounded by a shell. The blending amounts are shown in Table 1.
[0103] [Table 1]
[0104] As shown in Examples 1 to 12, it is understood that by containing an aromatic polymer (P1) obtained by polymerizing a monomer composition containing an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1), hollow resin particles having a hollow space surrounded by a shell and an average particle size of 0.1 μm to 5.0 μm can be obtained without using a high-boiling point compound such as hexadecane.
[0105] <Performance evaluation 1> To a mixture of 8.3 g of ethyl acetate and 1.7 g of solvent-soluble polyimide KPI-MX300F (Kawamura Sangyo Co., Ltd.), 1.6 g of ethyl acetate in which each particle was dispersed at a concentration of 10% by weight was added, and the mixture was degassed and stirred using a planetary mixer degasser (KURABO Corporation, Mazerustar KK-250) to prepare a mixture for evaluation. The mixture for evaluation was applied to a 5 mm thick glass plate using an applicator set to a wet thickness of 250 μm, and then heated at 60°C for 30 minutes, 90°C for 10 minutes, 150°C for 30 minutes, and 200°C for 30 minutes to remove ethyl acetate. Film samples containing each particle were then obtained by cooling to room temperature. The dielectric constant and dielectric loss tangent of the obtained films were evaluated using the cavity resonance method (measurement frequency: 5.8 GHz). The results are shown in Table 2.
[0106] [Table 2]
[0107] From the results in Table 2, it can be confirmed that the hollow resin particles provided by the present invention have the effect of lowering the relative dielectric constant and dielectric dissipation factor of the substrate, and are therefore effective for the purpose of reducing the dielectric constant and dielectric dissipation factor of the substrate.
[0108] <Performance evaluation 2> The slurries obtained in each of the Examples and Comparative Examples were dried using a Mini Spray Dryer B-290 (Nihon Buchi Co., Ltd.) to obtain hollow resin particles or particles as dry powder. 0.425 g of the obtained hollow resin particles or particles, 12.1 g of ethyl acetate, and 1.7 g of solvent-soluble polyimide KPI-MX300F (Kawamura Sangyo Co., Ltd.) were defoamed and stirred using a planetary stirring and defoaming machine (KURABO Corporation, Mazerustar KK-250) to prepare a mixture for evaluation. The mixture for evaluation was applied to a 5 mm thick glass plate using an applicator set to a wet thickness of 250 μm, and then heated at 60°C for 30 minutes, 90°C for 10 minutes, 150°C for 30 minutes, and 200°C for 30 minutes to remove ethyl acetate. Film samples containing each particle were then obtained by cooling to room temperature. The dielectric constant and dielectric loss tangent of the obtained films were evaluated using the cavity resonance method (measurement frequency: 5.8 GHz). The results are shown in Table 3.
[0109] [Table 3]
[0110] From the results in Table 3, it can be confirmed that the hollow resin particles provided by the present invention have the effect of lowering the relative dielectric constant of the substrate while suppressing an increase in the dielectric tangent compared to the particles (C1) of Comparative Example 1, and are therefore effective for the purpose of reducing the dielectric constant and dielectric tangent of the substrate. From these results, the relative dielectric constants of the hollow resin particles were calculated to be 1.90 for the hollow resin particles (1) of Example 1, 2.20 for the hollow resin particles (2) of Example 2, 1.93 for the hollow resin particles (3) of Example 3, 1.90 for the hollow resin particles (4) of Example 4, 2.20 for the hollow resin particles (7) of Example 7, and 2.28 for the particles (C1) of Comparative Example 1. The density of the substrate was 1.57 g / cm 3 It was calculated as:
[0111] <Performance evaluation 3> The slurries obtained in each of the Examples and Comparative Examples were dried using a Mini Spray Dryer B-290 (Nihon Buchi Co., Ltd.) to obtain hollow resin particles or particles as a dry powder. 0.4 g of the obtained hollow resin particles or particles and 10 g of ultra-high heat-resistant polyimide varnish (SPIXAREA HR002, Somar Co., Ltd.) were defoamed and stirred using a planetary stirring and defoaming machine (KURABO Corporation, Mazerustar KK-250) to prepare a mixture for evaluation. The mixture for evaluation was applied to a 5 mm thick glass plate using an applicator set to a wet thickness of 250 μm, and then heated at 120°C for 10 minutes, 180°C for 180 minutes, and 270°C for 60 minutes to remove the solvent, and then cooled to room temperature to obtain a film sample containing each particle. The dielectric constant and dielectric loss tangent of the obtained film were evaluated using the cavity resonance method (measurement frequency: 5.8 GHz). The results are shown in Table 4.
[0112] [Table 4]
[0113] From the results in Table 4, it can be confirmed that the hollow resin particles provided by the present invention have the effect of lowering the relative dielectric constant and dielectric dissipation factor of the substrate, and are therefore effective for the purpose of reducing the dielectric constant and dielectric dissipation factor of the substrate. [Industrial Applicability]
[0114] The hollow resin particles according to the embodiment of the present invention and the hollow resin particles obtained by the production method according to the embodiment of the present invention can be used as semiconductor materials, etc.
Claims
1. A hollow resin particle having a shell portion and a hollow portion surrounded by the shell portion, the shell portion comprises an aromatic polymer (P1) obtained by polymerizing a monomer composition comprising an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1), and a non-crosslinkable polymer (P2) which is at least one selected from the group consisting of polyolefins, styrene-based polymers, (meth)acrylic acid-based polymers, and styrene-(meth)acrylic acid-based polymers; Hollow resin particles. 【Chemistry 1】 (R 1 is H or CH 3 represents R 2 represents H, an alkyl group, or a phenyl group; R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms, and m represents the average number of moles of the oxyalkylene group added, which is a number from 1 to 100.
2. 2. The hollow resin particle according to claim 1, wherein the oxyalkylene group is at least one selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group.
3. 3. The hollow resin particle according to claim 1, wherein the monomer composition comprises 10% by weight to 70% by weight of an aromatic crosslinkable monomer (a), 10% by weight to 70% by weight of an aromatic monofunctional monomer (b), and 0.5% by weight to 30% by weight of a (meth)acrylic acid ester monomer (c) represented by general formula (1).
4. 4. The hollow resin particle according to claim 1, wherein the aromatic crosslinkable monomer (a) is divinylbenzene.
5. 5. The hollow resin particle according to claim 1, wherein the aromatic monofunctional monomer (b) is at least one selected from the group consisting of styrene and ethylvinylbenzene.
6. A method for producing hollow resin particles according to any one of claims 1 to 5, comprising the steps of: a monomer composition including an aromatic crosslinkable monomer (a), an aromatic monofunctional monomer (b), and a (meth)acrylic acid ester monomer (c) represented by formula (1), a non-crosslinkable polymer (P2) which is at least one selected from the group consisting of a polyolefin, a styrene-based polymer, a (meth)acrylic acid-based polymer, and a styrene-(meth)acrylic acid-based polymer, a polymerization initiator, and an organic mixed solution including an organic solvent having a boiling point of less than 100° C. are dispersed in an aqueous solution including at least one selected from the group consisting of a dispersion stabilizer and a surfactant, and suspension polymerization is performed; A method for producing hollow resin particles. 【Chemistry 2】 (R 1 is H or CH 3 represents R 2 represents H, an alkyl group, or a phenyl group; R 3 -O represents an oxyalkylene group having 2 to 18 carbon atoms, and m represents the average number of moles of the oxyalkylene group added, which is a number from 1 to 100.
7. A semiconductor material comprising the hollow resin particle according to any one of claims 1 to 5.
Citation Information
Patent Citations
Fine hollow polymer particle, production and use thereof
JP1990255704A
Emulsion particle having multilayer structure with core
JP1992211411A
Crosslinked resin particle, composition for organic insulation material, organic insulation material, sealant and circuit board
JP2000313818A
Crosslinked polymer particle powder and manufacturing method therefor
JP2005220213A
Hollow particles for light diffusion
WO2011040376A1